Enhanced heterologous protein productivity by genome reduction in Lactococcus lactis NZ9000. Issue 1 (December 2017) - Zhu, Duolong; Fu, Yuxin; Liu, Fulu; Xu, Haijin; Saris, Per; Qiao, Mingqiang
Abstract Background The implementation of novel chassis organisms to be used as microbial cell factories in industrial applications is an intensive research field.Lactococcus lactis, which is one of the most extensively studied model organisms, exhibits superior ability to be used as engineered host for fermentation of desirable products. However, few studies have reported about genome reduction ofL. lactis as a clean background for functional genomic studies and a model chassis for desirable product fermentation. Results Four large nonessential DNA regions accounting for 2.83% inL. lactis NZ9000 (L. lactis 9 k) genome (2, 530, 294 bp) were deleted using the Cre-loxP deletion system as the first steps toward a minimized genome in this study. The mutants were compared with the parental strain in several physiological traits and evaluated as microbial cell factories for heterologous protein production (intracellular and secretory expression) with the red fluorescent protein (RFP) and the bacteriocin leucocin C (LecC) as reporters. The four mutants grew faster, yielded enhanced biomass, achieved increased adenosine triphosphate content, and diminished maintenance demands compared with the wild strain in the two media tested. In particular, L. lactis 9 k-4 with the largest deletion was identified as the optimum candidate host for recombinant protein production. With nisin induction, not only the transcriptional efficiency but also the production levels of the expressed reporters were approximately three- to fourfold improved compared with the wild strain. The expression oflecC gene controlled with strong constitutive promoters P5 and P8 inL. lactis 9 k-4 was also improved significantly. Conclusions The genome-streamlinedL. lactis 9 k-4 outcompeted the parental strain in several physiological traits assessed. Moreover, L. lactis 9 k-4 exhibited good properties as platform organism for protein production. In future works, the genome ofL. lactis will be maximally reduced by using our specific design to provide an even more clean background for functional genomics studies thanL. lactis 9 k-4 constructed in this study. Furthermore, an improved background will be potentially available for use in biotechology.